Mounting of New Programme in Public Universities in Nigeria: Problems and Way Forward - Niyi Jacob Ogunode; AHMAD, Idris (Journal of Geography, Regional Planning and Development, 2024)
This paper titled "Mounting of New Programme in Public Universities in Nigeria: Problems and Way Forward" examined problems of mounting new programmes in the public universities in Nigeria. Secondary data were used. The secondary data were gathered from print materials and online publications. The paper concluded that funding, personnel, infrastructure facilities problems, National Universities Commission (NUC) bottleneck, lack of instructional resources and brain drain are the major problems that have affected the mounting of new programmes in Nigerian public universities. To address these problems, the paper suggested that public universities should be adequately funded to enable them to mount new programmes in their respective institutions. Adequate budgetary provisions should be made for the employment of personnel, provision of infrastructure facilities and instructional resources. Universities should be granted autonomy to enable them to develop their programme without interference from any institutions outside the universities.